Phylogeographic analysis in populations of Protonectarina sylveirae (Saussure, 1854) (Hymenoptera, Vespidae, Polistinae) - Silva, Marjorie da [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Ecological and historical processes of fauna diversification have been widely studied under the light of phylogeography, a discipline that deals with the spatial arrangements of genetic lineages. Swarm-founding wasps (Epiponini) as Protonectarina sylveirae (Saussure) are common representatives of Neotropical fauna. This species is widespread in Atlantic forest and presents a peculiar distribution within Epiponini because of its absence in Amazon region. Many studies point to the existence of recurrent phylogeographical discontinuities to different groups of organisms in Atlantic forest, but the explanations about events causing this patters remain inconclusive. This work aimed to investigate the phylogeographic pattern of P. sylveirae with special interest in presence of genetic structure, morphological differences among populations, and historical event(s) which could explain the observed phylogeographic pattern. Specimens of P. sylveirae were actively collected in 13 areas throughout its distribution for DNA extraction and amplification of mitochondrial genes 12S, 16S and COI. Analysis of genetic diversity, historical demography, divergence time, and population structure were performed. Twenty-two haplotypes were identified, a strong genetic structuration was found by the analysis of molecular variance (ANOVA) and the haplotype network revealed three haplotype groups, also corroborated by AMOVA. Analysis of historical demography showed that populations of P. sylveirae had remained constant throughout its evolutionary history. Differences were also found in morphology, corroborating partially those find by molecular data. Divergence time suggests earlier orogenic events occurred during the Tertiary as an important cause driven population diversification of P. sylveirae, and the role of aridization of forested areas in modeling the current distribution of populations.

Os processos históricos e ecológicos de diversificação da fauna têm sido amplamente estudados sob a luz da filogeografia, disciplina que lida com o arranjo espacial das linhagens genéticas. As vespas enxameadoras (Epiponini) como Protonectarina sylveirae (Saussure) são representantes comuns da fauna Neotropical. Esta espécie ocorre amplamente pela floresta Atlântica e apresenta uma distribuição peculiar dentro de Epiponini devido à sua ausência na região Amazônica. Apesar de muitos estudos apontarem para a existência de descontinuidades filogeográficas para diferentes organismos na floresta Atlântica, explicações sobre as causas de tais padrões permanecem inconclusivas. Este trabalho teve como objetivo investigar o padrão filogeográfico de P. sylveirae, com especial interesse na presença de estruturação genética e diferenciação morfológica, bem como nos eventos históricos que possam explicar o padrão filogeográfico observado. Os espécimes de P. sylveirae foram coletados ativamente em 13 áreas ao longo de sua distribuição para a extração, amplificação e sequenciamento dos genes mitocondriais 12S, 16S e COI. Foram realizadas analyses de diversidade genética, demografia histórica, tempo de divergência e estruturação populacional. Identificou-se 22 haplótipos, uma forte estruturação genética foi encontrada pela análise de variância molecular (AMOVA) e a rede de haplótipos revelou 3 grupos de haplótipos, também corroborados pela AMOVA. As análises de demografia mostraram estabilidade populacional para. Encontrouse diferenças na morfologia, corroborando parcialmente aquelas obtidas com os dados moleculares. A análise do tempo de divergência sugere que os eventos orogênicos do terciário e o processo de aridização das áreas de floresta que ocorreu a partir deste período influenciaram a diversificação e na atual configuração da distribuição das populações de P. sylveirae.
Análise filogeográfica em populações de Protonectarina sylveirae (Saussure, 1854) (Hymenoptera, Vespidae, Polistinae)
Keywords: Phylogeography; Neotropical Region; Quaternary; Filogeografia; Epiponini; Região Neotropical; mtDNA; Quaternário